2003
DOI: 10.1191/0961203303lu497oa
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive dysfunction and antiphospholipid antibodies in systemic lupus erythematosus

Abstract: Nervous system involvement in systemic lupus erythematosus (SLE) is typically diagnosed on the basis of clinical psychiatric and/or neurologic syndromes (NPSLE). Neuropsychological tests can be used to assess nervous system integrity even in the absence of major NP syndromes. Their application has uncovered significant cognitive dysfunction, ranging from mild to severe, in a sizeable proportion of SLE patients irrespective of clinical NP status. Cognitive dysfunction has now been accepted as a bona fide manife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
60
2
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 78 publications
9
60
2
3
Order By: Relevance
“…Nevertheless, there is no convincing data that confirms this hypothesis. 35,37,38 Published data on mice and humans and our own data obtained CD95 (Fas/Apo-1) controls neuronal branching C Zuliani et al from mice suggest that neurological deficits found in lpr mice are not a consequence of autoimmunity but a primary consequence of a nonfunctional CD95/CD95L system. Our data suggest an alternative explanation for observed cognitive deficits beyond an autoimmune explanation.…”
Section: Lack Of Cd95 Leads To Neurobehavioral Deficitsmentioning
confidence: 81%
See 1 more Smart Citation
“…Nevertheless, there is no convincing data that confirms this hypothesis. 35,37,38 Published data on mice and humans and our own data obtained CD95 (Fas/Apo-1) controls neuronal branching C Zuliani et al from mice suggest that neurological deficits found in lpr mice are not a consequence of autoimmunity but a primary consequence of a nonfunctional CD95/CD95L system. Our data suggest an alternative explanation for observed cognitive deficits beyond an autoimmune explanation.…”
Section: Lack Of Cd95 Leads To Neurobehavioral Deficitsmentioning
confidence: 81%
“…33,34 There is also evidence that a subgroup of SLE patients have cognitive impairments, including some without clinically obvious neuropsychiatry symptoms. 35,36 Also in humans, an increase in aPL was proposed to be the reason for the cognitive impairment. Nevertheless, there is no convincing data that confirms this hypothesis.…”
Section: Lack Of Cd95 Leads To Neurobehavioral Deficitsmentioning
confidence: 99%
“…The most direct evidence supporting the hypothesis of autoantibody involvement in NPSLE is derived from studies of animal models (13)(14)(15)(16)(17), whereas evidence from human studies is frequently conflicting or inconclusive (18)(19)(20)(21)(22). This may be due in part to methodologic difficulties involving, for example, selection of patients for study, lack of rigor in the characterization of NP events, and differences between laboratories in assay techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The latter include antiphospholipid antibodies (aPL), antiribosomal P antibodies (anti-P), and autoantibodies that bind to neuronal antigens such as the recently described antibodies to the NR2 glutamate receptor (13). Although there is biologic plausibility and data from in vitro studies and animal studies to implicate these autoantibodies in the causality of nervous system disease (13)(14)(15)(16)(17), studies of humans with SLE have yielded inconsistent findings (18)(19)(20)(21)(22). Previous investigations have been limited by their cross-sectional study design, heterogeneity of study patients in terms of disease duration, and lack of standardization in both the classification of NP events and the methodology used for autoantibody detection.…”
mentioning
confidence: 99%
“…Up to two-thirds of patients with SLE may have some form of neurologic or psychiatric manifestations of their disease 15, 2830 . Involvement of the central nervous system (CNS) can be caused by direct immune-mediated injury of tissues, systemic inflammatory mediators, vascular disease, and/or thromboembolic insults.…”
Section: The Unpredictable Course Of Slementioning
confidence: 99%